Spatial Layout, Social Structure, and Innovation in Organizations. (December 2014) - Wineman, Jean; Hwang, Yongha; Kabo, Felichism; Owen-Smith, Jason; Davis, Gerald F
Research on the enabling factors of innovation has most often addressed either the social component of organizations or the spatial dimensions involved in the innovation process. Few studies have examined the link from spatial layout and social networks to innovation. Social networks play important roles in structuring communication, collaboration, access to knowledge, and knowledge transformation. These processes are both antecedent to and part of the innovation process. Spatial layout structures patterns of circulation, proximity, awareness of others, and encounter in an organization. These interrelationships become fundamental to the development of social networks, especially those networks critical to the innovation process. This research explored associations between innovation within three partner organizations and the organization's social and spatial structure. The organizations included: A nonprofit life sciences institute dedicated to translational research on cancer, the research laboratories of a multinational software corporation, and the quality control group of an automobile manufacturer. The study applied spatial analysis to map and characterize physical space in conjunction with survey data capturing social contacts among researchers at the three organizations. For one partner organization, we augmented these tools with location-tracking methods. It could be argued that sociometric surveys capture the 'perceived' social network. Social networks researchers have been very interested in assessing 'real' networks either as reliability checks on sociometric survey networks, or as stand-alone networks. Our use of an ultrawideband location system allowed us to assess networks in real time. In interpreting our results, we suggest that through exposure to moving others, locations with high metric choice may provide the opportunities for serendipitous encounters among individuals who may come from disparate parts of an organization. Whereas low mean distance to others may provide the enhanced connections necessary to mobilize the resources and attention to move innovative ideas forward. Results demonstrate the salience of both social and spatial dimensions in the processes of innovation. The research suggests two strong factors that appear to influence our results: the institutional context which characterizes or prioritizes certain innovation outcomes; the extent to which the physical facility design of organizations tends to concentrate or spatially distribute the research unit. Our findings indicate that relationships between salutary network positions and beneficial locales themselves derive from institutional contexts that shape the priorities, opportunities, goals and practices of discovery. We suggest that innovation is a process that occurs at the intersection of social and physical space, and moves toward a sociospatial science of design for innovation.